Sustaining Open Educational Resources (OER) initiatives in Nigerian Universities. (4th May 2021) - Zaid, Yetunde A.; Alabi, Adefunke O.
ABSTRACT: Open educational resources (OERs) have increased in popularity and are becoming an important method of providing access to, and enhancing, the teaching and learning experience for both lecturers and students. Despite their popularity, approaches that may work best for sustaining OER initiatives in Nigerian universities are still evolving in Library and Information Science (LIS) literature. Considering the current budget climate for higher education in Nigeria, a framework that is tended towards the sustainability of OER needs to be developed. This article examines opportunities and threats surrounding OER, as well as highlighting major players in the OER landscape. A mixed method approach consisting of a survey and focus groups was used to gather both qualitative and quantitative information from academics and librarians at selected universities in Nigeria, who participated in the Nigerian Universities Commission's (NUC) OER ranking exercise. Data was analysed using descriptive statistics and thematic analysis respectively. While this paper provides recommendations based on findings on one hand, it also proffers suggestions for other libraries interested in growing OER initiatives focusing on development, implementation and assessment for universities operating with limited resources.